The politics of cultural representation - Burns, Rob (print, 2007)
This article considers the development of Turkish-German cinema, situating it in relation to both the early manifestations of a diasporic literature in Germany and the attempts by filmmakers associated with the New German Cinema to represent the experience of migrants in the Federal Republic. These films were frequently criticised for reducing their protagonists to stereotypes, portraying the migrant as victim and focusing excessively on conflict of an intercultural or intracultural kind. The 1990s saw the emergence of a younger generation of Turkish directors in Germany intent on breaking away from this
Aus: German politics ; 16.2007,3
Keywords: Deutschland; Germany; Multikulturelle Gesellschaft; Multicultural societies